Evaluasi Keberhasilan Penanaman Turus Jalan dalam Kota Kupang dengan Menggunakan Sistem Tanam Batang - Putri Rai Sae; Mamie Elsyana Pellondou; Nixon Rammang; Fadlan Pramatana (Wana Lestari, 2026)
Kupang City is experiencing a decline in environmental quality. This decline in environmental quality is caused by various factors such as an increase in land conversion to built-up land. The effect of decreasing environmental quality has an impact on various aspects of the urban spatial ecosystem. The high increase in land conversion causes a reduction in the quantity of green open space and gives rise to environmental problems such as increasing urban space temperatures and microclimate instability and so on. The local government, through policies, uses various alternatives to maintain the environmental stability of Kupang City, one of which is by providing city greening, including planting green lane vegetation using a stem planting system since 2018. This research aims to determine the success rate of the Kupang City road planting program. The data collected consisted of primary and secondary data using the spatial descriptive analysis method which was carried out from July to November 2022. Obstacles faced in managing the roadside planting program include the unmet need for green open space according to Kupang city area standards. In addition, if seen from The distribution of vegetation along the road, the percentage of plant growth of 64.96% is in the poor category, while the percentage of plant health is 50.54% in the low category. The results of the research show that the success of the Kupang City roadway planting program is in the medium category by achieving a total score of 70. The success rate of Kupang City roadway planting is Medium (the results of program implementation are accepted with the note that improvements need to be made until they reach a total value of > 80). Actions that need to be taken to overcome the obstacles experienced in planting road verges, especially regarding the condition of road vegetation in Kupang City, include the provision of regular replanting, pruning and maintenance activities.